Positive electrode material and preparation method thereof, positive electrode plate, battery and electric equipment

Through the doping technology of secondary lithiated sintered polymetallic element, the residual alkali problem in the preparation of high-nickel positive electrode materials is solved, and the structural stability and electrochemical performance are improved, the risks of the washing process and resource consumption are avoided, and the low Residual alkali, high-cycle stability high-nickel single-crystal positive electrode material.

CN119153667APending Publication Date: 2024-12-17JIANGSU DANGSHENG MATERIAL TECH CO LTD

Patent Information

Application Number
CN202411616150.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-13
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

The residual alkali problem caused by the increase in nickel content during the preparation process of high-nickel cathode materials affects the electrochemical performance and safety performance of lithium-ion batteries, and the traditional water washing process increases process risks and resource consumption.

Method used

The co-modified cathode material is doped by secondary lithiated sintering polymetallic elements. By doping Zr and Al elements during high-temperature sintering, the lithium-nickel mixed discharge effect is reduced, and the synergistic effect of Co(OH)2 and WO3 is used. Consumption of residual alkali and avoiding the water washing process, and prepare a high-nickel single-crystal positive electrode material with stable structure and low residual alkali.

Benefits of technology

It has achieved high cycle stability and electrochemical performance improvement, reduced residual alkali content and production costs, and avoided the risks and resource consumption of the washing process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119153667A_ABST
    Figure CN119153667A_ABST
Patent Text Reader

Abstract

The invention discloses a positive electrode material and a preparation method thereof, a positive electrode plate, a battery and electric equipment, the positive electrode material is of a layered structure of alpha-NaFeO2, in an XRD spectrum, characteristic peaks (006) and (102) in bimodal distribution are formed at the position of 2 theta being 37-39 degrees, and characteristic peaks (018) and (110) in bimodal distribution are formed at the position of 2 theta being 64-66 degrees; after the positive electrode material is circulated for 80 times under the conditions of 25 DEG C, 3.0 V-4. 3V and 1.0 C / 1.0 C, the change value of the cell parameter c / a meets # imgabs0 #. The positive electrode material disclosed by the invention has a relatively good layered structure and shows good crystallinity; and the material is stable in structure, even if the material is circulated for 80 weeks, the Li / Ni ion mixing degree of the material is slightly increased, the influence on the change of a wafer layer of a layered structure is small, the damage to a crystal structure is small, and the circulation retention rate is good.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the field of battery positive electrode materials, and specifically relates to a secondary lithiation sintered multi-metal element doped co-modified positive electrode material and its preparation method, positive electrode plate, battery and electrical equipment. Background Art

[0002] High-nickel layered nickel-cobalt-manganese-oxide ternary materials have a wide range of applications and have penetrated deeply into the field of new energy vehicles as the core power of green travel; at the same time, they also play an indispensable role in diversified fields such as power station energy storage power supply systems, consumer electronics market, uninterruptible power supply systems, and military equipment. However, the synthesis of high-nickel single crystal materials faces huge challenges, such as cation mixing, structural phase change, oxygen evolution reaction, microcracks, excessive residual alkali on the surface of the material, and the generation of impure Li5AlO4 phases.

[0003] Compared with traditional low-nickel positive electrode materials or 5 series ternary materials, high-nickel positive electrode materials are considered to be the first choice for positive electrode materials for power batteries because of their advantages such as low cobalt content, high specific capacity, and high operating voltage. However, during the preparation process of high-nickel positive electrode materials, as the nickel content increases, the residual alkali in the material will gradually increase, and a higher content of residual alkali will have an adverse effect on the electrochemical properties and safety performance of lithium-ion batteries. Therefore, the residual alkali problem has become the main obstacle to the large-scale application of high-nickel materials. At present, most high-nickel materials basically introduce water washing and secondary sintering coating processes on the basis of primary sintering. While reducing the residual alkali, additives are introduced for coating to prepare high-nickel positive electrode materials with low residual alkali content. However, the water washing process increases the process risk. The high-nickel material will react when it comes into contact with water and undergo Li + / H + Ion exchange delithiation the surface and near-surface regions of the material. The inward migration of protons causes the layered crystalline material to shrink in a direction perpendicular to the transition metal layer and the oxygen layer, while the outward migration of lithium leads to a decrease in the electrochemically active lithium of the material, thereby reducing the electrochemical performance of the positive electrode material.

[0004] In addition, during the electrochemical cycle, the residual alkali (such as LiOH) on the surface of the high-nickel positive electrode material will react with the main component of the electrolyte, LiPF6, to generate HF, which has a corrosive effect on the active electrode material. This substance can precipitate the transition metal ions in the NCM positive electrode material, destroy the layered structure of the positive electrode material, and thus deteriorate the rate performance and cycle stability of the positive electrode material. The currently commonly used coating materials such as metal oxides and metal phosphates are inert materials, so they will lead to a decrease in the capacity of the positive electrode material.

[0005] The purpose of the invention of this application is to obtain a high-nickel single crystal positive electrode material with stable structure and low residual alkali content by improving the existing preparation process. Summary of the invention

[0006] The present application aims to solve at least one of the technical problems in the related art to a certain extent. To this end, one purpose of the present application is to propose a secondary lithiation sintered multi-metal element doped co-modified positive electrode material and its preparation method, positive electrode plate, battery and electrical equipment.

[0007] In one aspect of the present application, the present application proposes a positive electrode material. According to an embodiment of the present application, the chemical formula of the positive electrode material is Li 1~1.2 Ni x Co y Mn z M a Al b Q c O2, wherein M is selected from one of Zr, Mg, Y and Ti, Q is selected from one of W, V and B, 0.6≤x<1.0, 0<y≤0.2, 0<z≤0.2, 0.001≤a<0.004, 0.004≤b<0.008, 0.001≤c<0.03; The positive electrode material is a layered structure of single crystal α-NaFeO2. In the XRD spectrum of the positive electrode material, there are characteristic peaks (006) and (102) with a bimodal distribution at 2θ of 37° to 39°, and there are characteristic peaks (018) and (110) with a bimodal distribution at 2θ of 64° to 66°. After the positive electrode material is cycled 80 times under the conditions of 25°C, 3.0V~4.3V, 1.0C / 1.0C, the change value of the unit cell parameter c / a satisfies , wherein a represents the length of the positive electrode material along the crystal a-axis before the cycle, c represents the length of the positive electrode material along the crystal c-axis before the cycle, a' represents the length of the positive electrode material along the crystal a-axis after 80 cycles, and c' represents the length of the positive electrode material along the crystal c-axis after 80 cycles.

[0008] The positive electrode material according to the embodiment of the present application has a good layered structure and exhibits good crystallinity; and its structure is stable. Even after 80 cycles, the increase in the Li / Ni ion mixing degree of the material is small, the change of the layered structure is small, the crystal structure is less damaged, the lithium ion migration is not greatly hindered, and the cycle retention rate is good. At the same time, by doping the above positive electrode material with Al elements and Zr 4+ The M element makes Zr 4+ Replace Ni 3 + Entering the layered structure, Zr 4+Doping causes the NCM lattice to expand, reduces the lithium-nickel mixing effect, increases the lithium-ion diffusion coefficient, and can also expand the layered structure and layer spacing of lithium nickel cobalt manganese oxide; Al 3+ doping with ions can inhibit the structural collapse of the material, increase the conductivity of the material, reduce the impedance during cycling, is beneficial to improving the conductivity, accelerating the diffusion and migration of Li + ions, and improve the battery performance. On the other hand, through the synergistic effect of Co element (such as Co(OH)2) and Q element (such as WO3), during the sintering process of the cathode material, the residual alkali is consumed through the reaction to obtain a high-nickel cathode single crystal material with a low residual alkali content. Using the cathode material of the present application as the cathode material of a lithium-ion battery effectively realizes high-cycle stability.

[0009] In addition, the cathode material according to the above embodiments of the present application may further have the following additional technical features: In some embodiments of the present application, in the XRD pattern of the cathode material, the ratio of the peak intensity I(003) of the (003) crystal plane to the peak intensity I(104) of the (104) crystal plane satisfies: 1.2 < I(003) / I(104) < 1.7; and / or, after the cathode material is cycled 80 times under the conditions of 25°C, 3.0V to 4.3V, and 1.0C / 1.0C, the change value of the I(003) / I(104) peak intensity ratio satisfies ; where I’(003) is the peak intensity of the characteristic peak corresponding to the (003) crystal plane of the cathode material after 80 cycles, and I’(104) is the peak intensity of the characteristic peak corresponding to the (104) crystal plane of the cathode material after 80 cycles.

[0010] In some embodiments of the present application, in the XRD pattern of the cathode material, the peak intensity I of the characteristic peak at 2θ = 33.7 - 34.0° a and the peak intensity I(003) of the (003) crystal plane satisfy: 0.001 ≤ I a / I(003) ≤ 0.1.

[0011] In some embodiments of the present application, the pH value of the cathode material is less than 11.7, the residual alkali content in the cathode material is less than 3500 ppm, the residual alkali in the cathode material includes LiOH and Li2CO3, and the ratio of the content of LiOH in the cathode material to the content of Li2CO3 in the cathode material is 0.1 - 0.8.

[0012] In some embodiments of the present application, the content of LiOH in the cathode material is less than 1100 ppm, and the content of Li2CO3 in the cathode material is less than 3000 ppm.

[0013] In the second aspect of the present application, the present application proposes a method for preparing the above-mentioned positive electrode material, comprising: (1) mixing a nickel-cobalt-manganese precursor, a portion of a lithium source, a metal doping element M source, and an Al source according to a stoichiometric ratio, and performing a first sintering to obtain a first sintered product; (2) The first sintered product, the remaining lithium source, the cobalt source and the metal coating element Q source are mixed according to a stoichiometric ratio to form a mixed material, and a second sintering is performed to obtain a single crystal positive electrode material.

[0014] According to the method for preparing the above-mentioned positive electrode material in the embodiment of the present application, the stability of the positive electrode material is improved by doping M source and Al source modification during the first lithiation process, while suppressing the mixed arrangement of lithium and nickel, and because the first lithiation sintering belongs to lithium-deficient sintering, which is different from the lithium-rich sintering of the traditional process, the residual alkali of the primary sintering material is reduced. At the same time, the present application uses the cobalt source supplemented during the secondary lithiation, which can further react with the lithium carbonate on the surface of the particles to form lithium cobaltate during the sintering process, so as to further reduce the residual alkali. In addition, the surface coating element Q (especially tungsten trioxide) can effectively increase the diffusion rate of lithium ions and improve the electrochemical properties of the material; at the same time, because tungsten trioxide has acidic activity, it can further react with the residual alkali on the surface of the high-nickel positive electrode particles, and a small amount of lithium tungstate can be generated, which synergistically reduces the residual alkali on the surface of the material. In this way, a high-nickel positive electrode material with low residual alkali and stable electrical properties can be obtained without water washing, reducing the indispensable water washing process in the traditional process.

[0015] Compared with the traditional method of reducing the residual alkali on the surface of high-nickel positive electrode material particles by water washing, the method of the present application reduces the residual alkali on the surface of the positive electrode material by improving the sintering process, without adding process equipment, optimizing and eliminating the water washing process, saving water resources and production costs.

[0016] In some embodiments of the present application, in step (1), the amount of the added lithium source satisfies the molar ratio of the Li element to the sum of the transition metal elements in the nickel-cobalt-manganese precursor of Li: (Ni + Co + Mn) = (0.85-0.95): 1; and / or, in step (1), the molar ratio of the Co element in the nickel-cobalt-manganese precursor to the sum of the transition metal elements in the nickel-cobalt-manganese precursor of Co: (Ni + Co + Mn) = (0.07-0.11) :1; and / or, in step (1), the amount of the Al source added satisfies the molar ratio of the Al element to the sum of the transition metal elements in the nickel-cobalt-manganese precursor of Al:(Ni+Co+Mn)=(0.004~0.008):1; and / or, in step (1), the amount of the M source added satisfies the molar ratio of the M element to the sum of the transition metal elements in the nickel-cobalt-manganese precursor of M:(Ni+Co+Mn)=(0.001~0.004):1.

[0017] In some embodiments of the present application, in step (2), the amount of the Co source added satisfies the following molar ratio in the compound: Co:(Ni+Co+Mn)=(0.10~0.14):1; and / or, in step (2), the amount of the remaining lithium source added satisfies the following molar ratio in the compound: Li:(Ni+Co+Mn)=(1.01~1.2):1; and / or, in step (2), the amount of the Q source added satisfies the following molar ratio in the compound: Q:(Ni+Co+Mn)=(0.001~0.03):1.

[0018] In some embodiments of the present application, the chemical formula of the nickel-cobalt-manganese precursor is Ni x Co y Mn z (OH)2, wherein 0.6≤x<1.0, 0<y≤0.2, 0<z≤0.2; and / or, the lithium source comprises LiOH·H2O, and the particle size D50 of the lithium source satisfies 12.0μm≤D50≤18.0μm; and / or, the metal doping element M source is an oxide, hydroxide, oxalate, organic alcohol salt or carbonate containing the M element, and the particle size D50 of the M source satisfies 0.5μm≤D50≤0.6μm; and / or, the Al source is selected from Al2O3, and the particle size D50 of Al2O3 satisfies 15nm≤D50≤25nm; and / or, the metal coating element Q source comprises WO3, and the particle size D50 of WO3 satisfies 30nm≤D50≤300nm; and / or, the cobalt source comprises cobalt hydroxide.

[0019] In some embodiments of the present application, in step (1), the first sintering is to first heat the temperature to 450°C~550°C in an oxygen atmosphere, keep the temperature for 4h~5h, then heat the temperature to 700°C~750°C, and keep the temperature for 10h~15h; and / or, the first sintered product is crushed, screened and iron-removed, and the particle size distribution of the first sintered product after crushing, screening and iron-removal satisfies: D1≥1.0μm, 3.0μm≤D50≤5.0μm, D100≤15.0μm, and the total content of magnetic foreign matter is ≤60ppm.

[0020] In some embodiments of the present application, in step (2), the second sintering is to heat the product to 730°C~800°C in an oxygen atmosphere and sinter for 10h~15h; and / or the second sintering product is crushed, screened and iron-removed to obtain the positive electrode material, and the particle size distribution of the positive electrode material satisfies: D1≥1.0μm, 3.0μm≤D50≤5.0μm, D100≤15.0μm, and the total content of magnetic foreign matter is ≤60ppm.

[0021] In the third aspect of the present application, the present application proposes a positive electrode plate. According to an embodiment of the present application, the positive electrode plate comprises the positive electrode material described in the first aspect of the present application or the positive electrode material prepared by the method described in the second aspect of the present application.

[0022] In a fourth aspect of the present application, the present application provides a battery. According to an embodiment of the present application, the battery includes the positive electrode sheet described in the third aspect of the present application.

[0023] In a fifth aspect of the present application, the present application proposes an electric device. According to an embodiment of the present application, the electric device includes the battery described in the fourth aspect of the present application.

[0024] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 This is a flow chart for preparing the secondary lithiation multi-metal doping co-modified positive electrode material according to an embodiment of the present application; Figure 2 The particle size quantity and volume distribution diagram of the ternary positive electrode of Example 1 and Comparative Examples 1-2 of the present application; Figure 3 The SEM images of the ternary positive electrode materials of Example 1 and Comparative Examples 1-2 of the present application; Figure 4 The XRD full spectrum detection analysis diagram of Example 1 and Comparative Examples 1-2 of the present application; Figure 5 This is the XRD full spectrum detection and analysis diagram after cycling of Example 1 and Comparative Examples 1-2 of the present application; Figure 6 These are performance diagrams of button cells at different rates according to Example 1 and Comparative Examples 1-2 of the present application; Figure 7 This is a graph of the capacity cycle performance of the button batteries of Example 1 and Comparative Examples 1-2 of the present application. DETAILED DESCRIPTION

[0026] Embodiments of the present application are described in detail below, and examples of the embodiments are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are intended to be used to explain the present application, and should not be construed as limiting the present application.

[0027] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0028] This application is proposed by the inventor based on the following issues: During the preparation of high-nickel positive electrode materials, as the nickel content increases, the residual alkali content of the material will gradually increase, and a higher content of residual alkali will have an adverse effect on the electrochemical performance and safety performance of lithium-ion batteries. In addition, based on the fact that a higher sintering temperature is required during the preparation of single crystals, in order to offset the volatilization of lithium during the high-temperature sintering process, it is also necessary to increase the amount of lithium added, but excessive lithium addition will increase the residual lithium content of the material, resulting in an increase in the residual alkali content of the material and an increase in battery gas production. Although water washing can reduce the surface lithium residue of the material, it will cause the delithiation of the high-nickel material, thereby causing structural defects on its surface.

[0029] In addition, single crystal materials require high temperatures during the sintering process, which will not only cause the primary particles to grow, but also cause the secondary particles to stick together, resulting in an increase in residual lithium and significant cation mixing. Although doping and annealing treatments can solve some problems arising from the synthesis of single crystal materials to a certain extent, when ternary materials containing the doping element Al are synthesized, excessive temperatures and excessive lithium content will cause the formation of Li5AlO4 impurity phases.

[0030] In addition, during the electrochemical cycle, the residual alkali (such as LiOH) on the surface of the high-nickel positive electrode material will react with the main component of the electrolyte, LiPF6, to generate HF, which has a corrosive effect on the active electrode material. This substance can precipitate the transition metal ions in the NCM positive electrode material, destroy the layered structure of the positive electrode material, and thus deteriorate the rate performance and cycle stability of the positive electrode material. The currently commonly used coating materials such as metal oxides and metal phosphates are inert materials, so they will lead to a decrease in the capacity of the positive electrode material.

[0031] In view of this, in one aspect of the present application, a secondary lithiation multi-metal doped co-modified positive electrode material is proposed. According to an embodiment of the present application, the chemical formula of the positive electrode material is Li 1~1.2 Ni x Co y Mn z M a Al b Q cO2, wherein M is selected from one of Zr, Mg, Y and Ti, Q is selected from one of W, V and B, 0.6≤x<1.0, 0<y≤0.2, 0<z≤0.2, 0.001≤a<0.004, 0.004≤b<0.008, 0.001≤c<0.03. The positive electrode material is a layered structure of single crystal α-NaFeO2. In the XRD spectrum of the positive electrode material, there are characteristic peaks (006) and (102) with a bimodal distribution at 2θ of 37°~39°, and characteristic peaks (018) and (110) with a bimodal distribution at 2θ of 64°~66°; after the positive electrode material is cycled 80 times under the conditions of 25°C, 3.0V~4.3V, and 1.0C / 1.0C, the change value of the unit cell parameter c / a satisfies , where a represents the length of the positive electrode material along the crystal a-axis before the cycle, c represents the length of the positive electrode material along the crystal c-axis before the cycle, a' represents the length of the positive electrode material along the crystal a-axis after 80 cycles, and c' represents the length of the positive electrode material along the crystal c-axis after 80 cycles. As a result, the positive electrode material has a good layered structure and exhibits good crystallinity; and its structure is stable. Even after 80 cycles, the increase in the Li / Ni ion mixing degree of the material is small, the change of the layered structure wafer layer is small, the crystal structure is less damaged, the lithium ion migration is not greatly hindered, and the cycle retention rate is good.

[0032] At the same time, by doping the above positive electrode materials with Al elements and M elements (such as Zr 4+ ), during the high temperature sintering process of the positive electrode material, Zr 4+ Replace Ni 3+ Entering the layered structure, Zr 4+ Doping expands the NCM lattice, reduces the lithium-nickel mixing effect, increases the lithium ion diffusion coefficient, and at the same time expands the layered structure and interlayer spacing of lithium nickel-cobalt-manganese oxide; Al 3+ Ion doping can inhibit the structural collapse of the material, improve the conductivity of the material, reduce the impedance during the cycle, and help improve the conductivity and accelerate Li + The diffusion and migration of ions improves battery performance. On the other hand, through the synergistic effect of Co element (such as Co(OH)2) and Q element (such as WO3), during the sintering process of the positive electrode material, the residual alkali is consumed by reaction to obtain a high-nickel positive electrode single crystal material with low residual alkali. The positive electrode material of the present application is used as the positive electrode material of the lithium-ion battery to effectively achieve high cycle stability. The cycle performance of the positive electrode material was tested at 25°C 1.0 C. After 80 cycles, the discharge specific capacity was as high as 204.6 mAh / g, and the capacity retention rate was as high as 100.03%.

[0033] According to some specific embodiments of the present application, in the XRD pattern of the positive electrode material, the ratio of the peak intensity I(003) of the (003) crystal plane to the peak intensity I(104) of the (104) crystal plane satisfies: 1.2 < I(003) / I(104) < 1.7; after the positive electrode material is cycled 80 times under the conditions of 25°C, 3.0V - 4.3V, and 1.0C / 1.0C, the change value of the I(003) / I(104) peak intensity ratio satisfies ; where I’(003) is the peak intensity of the characteristic peak corresponding to the (003) crystal plane of the positive electrode material after 80 cycles, and I’(104) is the peak intensity of the characteristic peak corresponding to the (104) crystal plane of the positive electrode material after 80 cycles. Thus, the present application effectively inhibits the lattice distortion caused by phase transformation during charge and discharge of the NCM positive electrode material, has good structural stability, can prevent the generation and expansion of microcracks, and improves the cycle stability of the material. The special structure of the positive electrode material of the present application effectively reduces structural degradation, enhances mechanical and chemical stability, improves cycle stability and Li + diffusion kinetics, and thus exhibits excellent comprehensive electrochemical performance and stability. In terms of structural stability, from in-situ XRD, after cycling 80 times at 25°C, 3.0V - 4.3V, and 1.0C / 1.0C, the change value of I(003) / I(104) is small, and its c / a is basically the same, indicating that the cycle performance and structure of the positive electrode material are also relatively stable.

[0034] According to still some other specific embodiments of the present application, in the XRD pattern of the positive electrode material, the ratio of the peak intensity I of the characteristic peak at 2θ = 33.7° - 34.0° a to the peak intensity I(003) of the (003) crystal plane satisfies: 0.001 ≤ I a / I(003) ≤ 0.1. It shows that the generation of the impurity phase Li5AlO4 is effectively inhibited in the positive electrode material.

[0035] According to yet some other specific embodiments of the present application, the pH value of the positive electrode material is less than 11.7, the residual alkali content in the positive electrode material is less than 3500 ppm, and the residual alkali in the positive electrode material includes LiOH and Li2CO3. Thus, the positive electrode material of the present application has a low soluble residual alkali content, can avoid the increase in the content of non-electrochemically active substances in the positive electrode material caused by too high content of soluble alkali on the surface of the positive electrode material, thereby resulting in the reduction of the charge and discharge capacity of the lithium-ion battery containing the positive electrode material; at the same time, it can also avoid the reduction of the rate performance caused by the increase in the thickness of the inert layer on the surface of the positive electrode material and the impedance of the positive electrode material due to too high surface soluble alkali content. Further, the ratio of the content of LiOH in the residual alkali to the content of Li2CO3 in the residual alkali is 0.1 - 0.8.

[0036] As some preferred embodiments, the content of LiOH in the positive electrode material is less than 1100 ppm, and the content of Li2CO3 in the positive electrode material is less than 3000 ppm, thereby further reducing the soluble residual alkali content in the positive electrode material.

[0037] According to some other specific embodiments of the present application, the above-mentioned positive electrode material includes an inner layer positive electrode material and an outer layer positive electrode material, the Q element is located in the outer layer positive electrode material, and the concentration of the Co element in the outer layer positive electrode material is higher than the concentration of the Co element in the inner layer positive electrode material.

[0038] In the second aspect of the present application, the present application proposes a method for preparing the above-mentioned positive electrode material. According to the embodiments of the present application, referring to the attached Figure 1 , the method comprising: S100: mixing a nickel-cobalt-manganese precursor, a portion of a lithium source, a metal doping element M source, and an Al source according to a stoichiometric ratio, and performing a first sintering to obtain a first sintered product; In this step, the nickel-cobalt-manganese precursor, part of the lithium source, the metal doping element M source, and the Al source can be added to a high-speed mixer according to a stoichiometric ratio, and mixed until each component is fully and evenly dispersed to obtain a mixed material, and then the first sintering is performed in an oxygen atmosphere to obtain a first sintered product.

[0039] In the embodiments of the present application, the doping of metal doping elements M source and Al source can effectively improve the cycle and stability performance of the positive electrode material. In particular, the present application modifies the positive electrode material by doping ZrO2 and Al2O3, so that Zr 4+ Replace Ni 3+ Entering the layered structure, Zr 4+ Doping expands the NCM lattice, reduces the lithium-nickel mixing effect, and increases the lithium ion diffusion coefficient. At the same time, it can expand the layered structure and interlayer spacing of lithium nickel-cobalt-manganese oxide. 3+ Ion doping can inhibit the structural collapse of the material. The preparation method can reduce the generation of Li5AlO4 impurity phase, improve the conductivity of the material, reduce the impedance during the cycle, and help improve the conductivity and accelerate the Li + The diffusion and migration of ions improves battery performance. In addition, Al2O3, as a stable metal oxide, can effectively inhibit the contact between organic electrolyte and positive electrode materials and inhibit the decomposition of electrolyte.

[0040] According to some specific embodiments of the present application, in step S100, the amount of added lithium source satisfies the molar ratio of Li element to the sum of transition metal elements in the nickel-cobalt-manganese precursor of Li:(Ni+Co+Mn)=(0.85~0.95):1, preferably 0.9:1, and the molar ratio of Co element in the nickel-cobalt-manganese precursor to the sum of transition metal elements in the nickel-cobalt-manganese precursor is Co:(Ni+Co+Mn)=(0.07~0.11):1, preferably 0.09:1, that is, the first sintering is in a lithium-deficient state to prevent the generation of residual alkali due to excessive lithium source, and lithium is supplemented during the second sintering. The two-stage lithiation sintering can reduce the alkali content of the positive electrode material.

[0041] According to some further specific embodiments of the present application, in step S100, the amount of M source added satisfies the molar ratio of M element to the sum of transition metal elements in the nickel-cobalt-manganese precursor of M:(Ni+Co+Mn)=(0.001~0.004):1; the amount of Al source added satisfies the molar ratio of Al element to the sum of transition metal elements in the nickel-cobalt-manganese precursor of Al:(Ni+Co+Mn)=(0.004~0.008):1.

[0042] According to some other specific embodiments of the present application, in step S100, the first sintering is to first heat the temperature to 450°C~550°C (as an example, it can be 450°C, 460°C, 470°C, 480°C, 490°C, 500°C, 510°C, 520°C, 530°C, 540°C, 550°C, etc.) in an oxygen atmosphere, and keep the temperature for 4h~5h (as an example, it can be 4h, 4.2h, 4.4h, 4.5h, 4.6h, 4.8h, 5h, etc.), and perform pre-sintering, the purpose of which is to remove the bound water in the reaction raw material system. Then heat the temperature to 700°C~750°C (as an example, it can be 700°C, 710°C, 720°C, 730°C, 740°C, 750°C, etc.), and keep the temperature for 10h~15h (as an example, it can be 10h, 11h, 12h, 13h, 14h, 15h, etc.). Preferably, the temperature is first raised to 550° C. and kept at this temperature for 5 hours for pre-sintering, and then the temperature is raised to 720° C. and kept at this temperature for 10 hours. Furthermore, the kiln is an atmosphere furnace with an oxygen concentration of ≥ 99.0%.

[0043] In the embodiment of the present application, the chemical formula of the nickel-cobalt-manganese precursor is Ni x Co y Mn z (OH)2, where 0.6≤x<1.0, 0<y≤0.2, 0<z≤0.2.

[0044] In the embodiments of the present application, the specific type of the lithium source is not particularly limited. As a preferred embodiment, the lithium source includes LiOH·H2O, and the particle size D50 of the lithium source satisfies 12.0μm≤D50≤18.0μm. Furthermore, the content of LiOH in the lithium source accounts for 55wt%~57wt%.

[0045] In the embodiments of the present application, the specific type of the above-mentioned metal doping element M source is not particularly limited, and the metal doping element M source can be an oxide, hydroxide, oxalate, organic alcohol salt or carbonate containing element M. As a preferred embodiment, the metal doping element M source includes ZrO2, and the particle size D50 of ZrO2 satisfies 0.5μm≤D50≤0.6μm. Furthermore, the purity of ZrO2 is ≥99.5%.

[0046] In the embodiment of the present application, the specific type of the second doping element Al source is not particularly limited. As a preferred embodiment, the second doping element Al source includes Al2O3, and the particle size D50 of Al2O3 satisfies 15nm≤D50≤25nm. Furthermore, the purity of Al2O3 is ≥99.9%.

[0047] According to some further specific embodiments of the present application, step S100 further includes: The first sintered product is crushed to a certain particle size by jet milling, and after vibrating screening, the magnetic foreign matter is reduced by an iron remover to obtain a first sintered product with uniform particle dispersion. The particle size distribution of the first sintered product after crushing, screening and iron removal meets the following requirements: D1 ≥ 1.0 μm, 3.0 μm ≤ D50 ≤ 5.0 μm, D100 ≤ 15.0 μm, and the total content of magnetic foreign matter (such as Fe, Zn, Cu, etc.) ≤ 60 ppm.

[0048] S200: mixing the first sintered product, the remaining lithium source, the cobalt source and the metal coating element Q source according to a stoichiometric ratio to form a mixed material, and performing a second sintering to obtain a single crystal positive electrode material; In this step, the remaining lithium source and cobalt source can be added to the first sintered product in a stoichiometric ratio, and after being evenly dispersed in a high-speed mixer, the metal coating element Q source is added, mixed and dispersed at high speed again, and then sintered for the second time in an oxygen atmosphere to obtain a single crystal positive electrode material.

[0049] According to some specific embodiments of the present application, in step S200, the amount of the remaining lithium source added satisfies the molar ratio in the compound material: Li:(Ni+Co+Mn)=(1.01~1.2):1, and the amount of the Co source added satisfies the molar ratio in the compound material: Co:(Ni+Co+Mn)=(0.10~0.14):1, preferably Co:(Ni+Co+Mn)=0.12:1. The first sintering is in a lithium-deficient state to prevent the generation of residual alkali due to excessive lithium source, and lithium is supplemented during the second sintering. The two-stage lithiation sintering can reduce the alkali content of the positive electrode material. At the same time, the present application utilizes the process of secondary lithiation, by supplementing the remaining cobalt source, the cobalt hydroxide supplemented into the system is dehydrated at a specific temperature to generate cobalt oxide, a part of the cobalt source reacts with the supplemented LiOH and the precursor, and its crystal structure continues to grow on the basis of the primary particles, increasing the structural strength of the particles and forming a single crystal, while a small part of the cobalt oxide can further react with the residual alkali (Li2CO3) on the surface of the particles to generate lithium cobaltate, thereby achieving the purpose of reducing the residual alkali through a reaction.

[0050] According to some further specific embodiments of the present application, in step S200, the amount of Q source added satisfies the following molar ratio in the mixed material: Q:(Ni+Co+Mn)=(0.001~0.03):1.

[0051] According to some further specific embodiments of the present application, in step S200, the second sintering is to heat the steel to 730°C to 800°C (as an example, it can be 730°C, 740°C, 750°C, 760°C, 770°C, 780°C, 790°C, 800°C, etc.) in an oxygen atmosphere and sinter for 10h to 15h (as an example, it can be 10h, 11h, 12h, 13h, 14h, 15h, etc.). The second sintering temperature is preferably 780°C, and the sintering time is 10h. Furthermore, the kiln is an atmosphere furnace, and the oxygen concentration is ≥99.0%.

[0052] In the embodiments of the present application, the specific type of the metal-coated element Q source is not particularly limited. As a preferred embodiment, the metal-coated element Q source includes WO3, and the particle size D50 of WO3 satisfies 30nm≤D50≤300nm. Furthermore, the purity of WO3 is ≥99.9%. Tungsten trioxide is composed of tungsten oxide octahedrons connected end to end, and the gaps between the octahedrons can be used as Li +The transmission channel of lithium ions is increased, and the diffusion rate of lithium ions is increased, thereby improving the electrochemical properties of the material. In addition, tungsten trioxide is an acidic oxide that can resist the corrosion of the electrolyte HF on the positive electrode material, reduce the interfacial reaction between the positive electrode material and the electrolyte, and further improve the interfacial stability of the material. The inventors found that tungsten oxide has the best effect on inhibiting lithium-nickel mixing. High-valent tungsten oxide is conducive to the increase of trivalent nickel on the surface. At the same time, in terms of lattice oxygen or the inhibition of oxygen defects, high-valent metal tungsten oxide is more effective, because the bond energy formed by high-valent tungsten oxide and oxygen is stronger, and tungsten oxide has better inhibition of lattice oxygen deficiency. Moreover, after tungsten trioxide is coated, it can still maintain a relatively good layered structure, and there is no rock salt phase with poor effect due to the coating.

[0053] In the embodiments of the present application, the specific type of the above-mentioned cobalt source is not particularly limited. As a preferred embodiment, the cobalt source includes cobalt hydroxide.

[0054] According to some further specific embodiments of the present application, step S200 further includes: The second sintered product is crushed to a certain particle size by air jet mill, and then screened by vibration screen and iron remover to reduce magnetic foreign matter, so as to obtain positive electrode material with uniform particle dispersion. The particle size distribution of the positive electrode material satisfies: D1 ≥ 1.0 μm, 3.0 μm ≤ D50 ≤ 5.0 μm, D100 ≤ 15.0 μm, and the total content of magnetic foreign matter (such as Fe, Zn, Cu, etc.) ≤ 60 ppm.

[0055] According to the method for preparing the positive electrode material of the embodiment of the present application, by doping M element and Al2O3 modification during the first lithiation process, the mixed arrangement of lithium and nickel is suppressed, and the stability of the positive electrode material is improved. Due to the first lithiation sintering, the ratio of Li: (Ni + Co + Mn) = (0.85 ~ 0.95): 1 < 1 in the material, the system actually belongs to a lithium-deficient sintering, which is different from the lithium-rich sintering of the traditional process, thereby reducing the residual alkali of the primary sintering material. At the same time, the present application utilizes the cobalt hydroxide supplemented during the secondary lithiation, which can further react with the lithium carbonate on the surface of the particles to form lithium cobaltate during the sintering process, thereby achieving the purpose of further reducing the residual alkali. In addition, the surface coating of tungsten trioxide can effectively increase the diffusion rate of lithium ions and improve the electrochemical properties of the material; at the same time, because tungsten trioxide has acidic activity, it can further react with the residual alkali on the surface of the high-nickel positive electrode particles, and a small amount of lithium tungstate can be generated, which synergistically reduces the residual alkali on the surface of the material. In this way, a high-nickel positive electrode material with low residual alkali and stable electrical properties can be obtained without water washing, reducing the indispensable water washing process in the traditional process.

[0056] At the same time, the present invention modifies the M element and Al2O3 by doping, so that the M ions replace the Ni in the high temperature sintering process. 3+Entering the layered structure, the doping of M element causes the NCM lattice to expand, reducing the lithium-nickel mixing effect and increasing the lithium ion diffusion coefficient. At the same time, it can expand the layered structure and interlayer spacing of nickel-cobalt-manganese oxide lithium. 3+ Ion doping can inhibit the structural collapse of the material. At the same time, the preparation process (secondary lithiation method) of the present application can reduce the generation of Li5AlO4 impurity phase, improve the conductivity of the material, reduce the impedance during the cycle, and help to improve the conductivity and accelerate Li + Diffusion and migration of ions improve battery performance.

[0057] Compared with the traditional method of reducing the residual alkali on the surface of high-nickel positive electrode material particles by water washing, the method of the present application reduces the residual alkali on the surface of the positive electrode material by improving the sintering process, without adding process equipment, optimizing and eliminating the water washing process, saving water resources and production costs.

[0058] In the third aspect of the present application, the present application proposes a positive electrode plate. According to an embodiment of the present application, the positive electrode plate includes a positive electrode current collector and a positive electrode active material layer disposed on at least one side of the positive electrode current collector, and the positive electrode active material layer includes the positive electrode material described in the first aspect of the present application, or a positive electrode material prepared by the method described in the second aspect.

[0059] According to an embodiment of the present application, the positive electrode plate includes a positive electrode current collector and a positive electrode active material layer arranged on the positive electrode current collector, the positive electrode active material layer includes the above-mentioned positive electrode material, wherein the positive electrode current collector can be a metal foil or a composite current collector (the metal material can be arranged on a polymer substrate to form a composite current collector), for example, the positive electrode current collector can be aluminum foil.

[0060] According to some embodiments of the present application, the positive electrode active material layer may further optionally include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, or fluorine-containing acrylate resin.

[0061] According to some embodiments of the present application, the positive electrode active material layer may further optionally include a conductive agent. As an example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, or carbon nanofibers.

[0062] According to some embodiments of the present application, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode material, the conductive agent, the binder and any other components, are dispersed in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, cold pressing and other processes, the positive electrode sheet can be obtained.

[0063] It should be noted that the features and advantages described above for the positive electrode material and its preparation method are also applicable to the positive electrode plate and will not be repeated here.

[0064] In the fourth aspect of the present application, the present application proposes a battery. According to an embodiment of the present application, the battery includes at least one of the positive electrode sheets of the third aspect. Thus, the discharge efficiency, capacity retention rate, rate performance and cycle performance of the battery can be effectively improved.

[0065] As an example, a battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator, and the separator is located between the positive electrode sheet and the negative electrode sheet. During the charge and discharge process of the battery, active ions are embedded and removed back and forth between the positive electrode sheet and the negative electrode sheet. The electrolyte plays the role of conducting ions between the positive electrode sheet and the negative electrode sheet. The separator is arranged between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, while allowing ions to pass through.

[0066] According to an embodiment of the present application, the negative electrode plate includes a negative electrode current collector and a negative electrode active material layer arranged on the negative electrode current collector, the negative electrode active material layer includes a negative electrode active material, wherein the negative electrode current collector can be a metal foil or a composite current collector (the metal material can be arranged on a polymer substrate to form a composite current collector), for example, the negative electrode current collector can be a copper foil.

[0067] According to some embodiments of the present application, the negative electrode active material may include at least one of the following materials: artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, sodium titanate, etc.

[0068] According to some embodiments of the present application, the negative electrode active material layer may further include a conductive agent, which may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, or carbon nanofibers.

[0069] According to some embodiments of the present application, the negative electrode active material layer may optionally further include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).

[0070] According to some embodiments of the present application, the negative electrode sheet can be prepared in the following manner: the above-mentioned components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, and the adhesive are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.

[0071] According to some other embodiments of the present application, there is no particular restriction on the type of isolation membrane, and any known porous structure isolation membrane with good chemical stability and mechanical stability can be selected. As an example, the material of the isolation membrane may include at least one of glass fiber, non-woven fabric, polyethylene, polypropylene or polyvinylidene fluoride. The isolation membrane can be a single-layer film or a multi-layer composite film without particular restriction. When the isolation membrane is a multi-layer composite film, the materials of each layer can be the same or different without particular restriction.

[0072] According to some other embodiments of the present application, the type of electrolyte is not specifically limited and can be selected according to needs. According to some specific embodiments of the present application, the electrolyte is an electrolyte solution, and the electrolyte solution includes a lithium salt and a solvent.

[0073] According to some specific embodiments of the present application, the lithium salt may include lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium bis(fluorosulfonyl)imide (LiFSI), lithium phosphate (LiBOB), lithium difluorophosphate (LiPO2F2) According to some specific embodiments of the present application, the solvent may include at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, ethylene glycol dimethyl ether, methyl ethyl sulfone or diethyl sulfone.

[0074] In some embodiments of the present application, the electrolyte may further include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, and may also include additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.

[0075] It should be noted that the above-mentioned features and advantages described for the positive electrode plate are also applicable to the battery and will not be repeated here.

[0076] In a fifth aspect of the present application, the present application proposes an electric device. According to an embodiment of the present application, the electric device includes the above-mentioned battery. The features and advantages described above for the battery are also applicable to the electric device and will not be repeated here.

[0077] Specifically, the electrical equipment may be, but is not limited to, mobile phones, tablets, laptops, electric toys, electric tools, battery cars, electric cars, ships, spacecraft, etc. Electric toys may include fixed or mobile electric toys, such as game consoles, electric car toys, electric ship toys, and electric airplane toys, etc. Spacecraft may include airplanes, rockets, space shuttles, and spacecraft, etc.

[0078] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.

[0079] Example 1 In this embodiment, the lithium source and the cobalt source are supplemented by the secondary lithiation method to prepare the ternary positive electrode material, and its chemical formula is: Li 1.03 Ni 0.83 Co 0.12 Mn 0.05 Zr 0.0016 Al 0.0058 W 0.0016 O2, the preparation method of the ternary positive electrode material comprises the following steps: 1) Ni 0.86 Co 0.09 Mn 0.05 (OH)2 precursor, LiOH, ZrO2, Al2O3 are mixed to prepare a compound material, wherein LiOH and precursor Ni 0.86 Co 0.09 Mn 0.05 The molar ratio of (OH)2 is Li: (Ni + Co + Mn) = 0.9:1; in terms of molar ratio, the amount of ZrO2 satisfies Zr: (Ni + Co + Mn) = 0.0016:1, and the amount of Al2O3 satisfies Al: (Ni + Co + Mn) = 0.0058:1.

[0080] 2) The mixed materials are placed in a sagger of 330*330*120mm and sintered in an oxygen atmosphere furnace. The sintering conditions are: the kiln is first heated to 550℃ and kept warm for 5h, then heated to 720℃ and kept warm for 10h. The kiln is an atmosphere furnace with an oxygen concentration of ≥99.0%.

[0081] 3) The obtained sintered material is crushed, and cobalt hydroxide is added in a molar ratio until the Co: (Ni + Co + Mn) in the mixed material is 0.12:1, and a lithium source (LiOH) is added until the Li: (Ni + Co + Mn) in the mixed material is 1.03:1, and the mixture is dispersed at high speed for 30 minutes; then WO3 powder is added, and the amount of WO3 in a molar ratio satisfies W: (Ni + Co + Mn) = 0.0016:1, and the mixture is evenly mixed and dispersed.

[0082] 4) The obtained coated material is subjected to a second lithium sintering reaction, specifically, the kiln is heated to 780°C and sintered for 10 hours. The kiln is an atmosphere furnace with an oxygen concentration of ≥99.0%; the sintered material is then crushed and sieved to remove iron to obtain a secondary lithium low residual alkali positive electrode material; recorded as SC1-NCM.

[0083] Example 2 The preparation method of this embodiment is basically the same as that of embodiment 1, except that: 1) Ni precursor 0.86 Co 0.09 Mn 0.05 (OH)2 and LiOH are in a molar ratio of Li:(Ni+Co+Mn)=0.85:1.

[0084] The prepared ternary cathode material is recorded as SC2-NCM, and its chemical formula is: Li 1.03 Ni 0.83 Co 0.12 Mn 0.05 Zr 0.0016 Al 0.0058 W 0.0016 O2.

[0085] Example 3 The preparation method of this embodiment is basically the same as that of embodiment 1, except that: 1) Ni precursor 0.86 Co 0.09 Mn 0.05 (OH)2 and LiOH are in a molar ratio of Li:(Ni+Co+Mn)=0.95:1.

[0086] The prepared ternary cathode material is recorded as SC3-NCM, and its chemical formula is: Li 1.03 Ni 0.83 Co 0.12 Mn 0.05 Zr 0.0016 Al 0.0058 W 0.0016 O2.

[0087] Example 4 The preparation method of this embodiment is basically the same as that of embodiment 1, except that: 3) Add lithium source (LiOH) until the mixture has a molar ratio of Li: (Ni+Co+Mn) = 1.05:1.

[0088] The prepared ternary cathode material is recorded as SC4-NCM, and its chemical formula is: Li 1.05 Ni 0.83 Co 0.12 Mn 0.05 Zr 0.0016 Al 0.0058 W 0.0016 O2.

[0089] Example 5 The preparation method of this embodiment is basically the same as that of embodiment 1, except that: 3) Add lithium source (LiOH) until the mixture has a molar ratio of Li: (Ni + Co + Mn) = 1.15:1.

[0090] The prepared ternary cathode material is recorded as SC5-NCM, and its chemical formula is: Li 1.15 Ni 0.83 Co 0.12 Mn 0.05 Zr 0.0016 Al 0.0058 W 0.0016 O2.

[0091] Example 6 The preparation method of this embodiment is basically the same as that of embodiment 1, except that: 3) Add cobalt hydroxide in a molar ratio until the ratio of Co: (Ni + Co + Mn) in the mixed material is 0.10:1.

[0092] The prepared ternary cathode material is recorded as SC6-NCM, and its chemical formula is: Li 1.03 Ni 0.85 Co 0.1 Mn 0.05 Zr 0.0016 Al 0.0058 W 0.0016 O2.

[0093] Example 7 The preparation method of this embodiment is basically the same as that of embodiment 1, except that: 3) Add cobalt hydroxide in a molar ratio until the ratio of Co: (Ni + Co + Mn) in the mixture is 0.14:1.

[0094] The prepared ternary cathode material is recorded as SC7-NCM, and its chemical formula is: Li 1.03 Ni 0.82 Co 0.14Mn 0.04 Zr 0.0016 Al 0.0058 W 0.0016 O2.

[0095] Example 8 (M element is Ti) The preparation method of this embodiment is basically the same as that of embodiment 1, except that: The amount of TiO2 used satisfies Ti: (Ni + Co + Mn) = 0.31:100 to prepare the mixed material.

[0096] The prepared ternary cathode material is recorded as SC8-NCM, and its chemical formula is: Li 1.03 Ni 0.83 Co 0.12 Mn 0.05 Ti 0.0031 Al 0.0058 W 0.0016 O2.

[0097] Example 9 (Q source is V2O5) The preparation method of this embodiment is basically the same as that of embodiment 1, except that: 3) Add V2O5 powder, and the amount of V2O5, calculated by molar ratio, should satisfy V: (Ni + Co + Mn) = 0.0057:1.

[0098] The prepared ternary cathode material is recorded as SC9-NCM, and its chemical formula is: Li 1.03 Ni 0.83 Co 0.12 Mn 0.05 Zr 0.0016 Al 0.0058 V 0.0057 O2.

[0099] Example 10 (precursor is 9 series product) The preparation method of this embodiment is basically the same as that of embodiment 1, except that: 1) According to the stoichiometric ratio, the precursor Ni 0.90 Co 0.05 Mn 0.05 (OH)2, LiOH, ZrO2 and Al2O3 are mixed to prepare a compound material.

[0100] The prepared ternary cathode material is recorded as SC10-NCM, and its chemical formula is: Li 1.03 Ni 0.83 Co 0.12 Mn 0.05 Zr 0.001 6Al 0.0058 W 0.0016 O2.

[0101] Example 11 (precursor is 6 series product) The preparation method of this embodiment is basically the same as that of embodiment 1, except that: 1) According to the stoichiometric ratio, the precursor Ni 0.65 Co 0.07 Mn 0.28 (OH)2, LiOH, ZrO2 and Al2O3 are mixed to prepare a compound material.

[0102] The prepared ternary cathode material is recorded as SC11-NCM, and its chemical formula is: Li 1.03 Ni 0.60 Co 0.12 Mn 0.25 Zr 0.001 6Al 0.0058 W 0.0016 O2.

[0103] Comparative Example 1 This comparative example prepares a ternary positive electrode material according to a single lithiation, and its chemical formula is: LiNi 0.83 Co 0.12 Mn 0.05 Zr 0.0016 Al 0.0058 W 0.0016 The difference from Example 1 is that, in terms of molar ratio, the Co content in the precursor of this comparative example satisfies: Co: (Ni + Co + Mn) = 0.12: 1, and the amount of Li element added in step 1) is Li: (Ni + Co + Mn) = 1.03: 1.

[0104] The preparation method of the ternary positive electrode material comprises the following steps: 1) Ni precursor 0.83 Co 0.12 Mn 0.05 A mixture of (OH)2 and LiOH is prepared according to the molar ratio of Li: (Ni + Co + Mn) = 1.03:1; the amount of ZrO2 added therein, calculated on a molar ratio, satisfies Zr: (Ni + Co + Mn) = 0.0016:1, and the amount of Al2O3 satisfies Al: (Ni + Co + Mn) = 0.0058:1.

[0105] 2) The mixed materials are placed in a sagger of 330*330*120mm and sintered in an oxygen atmosphere furnace. The sintering conditions are: the kiln is first heated to 550℃ and kept warm for 5h, then heated to 720℃ and kept warm for 10h. The kiln is an atmosphere furnace with an oxygen concentration of ≥99.0%.

[0106] 3) The obtained sintered material is crushed into a certain particle size, and WO3 is added, wherein the amount of WO3 satisfies W: (Ni + Co + Mn) = 0.0016:1 in terms of molar ratio, and the mixture is evenly mixed and dispersed.

[0107] 4) The obtained coated material is subjected to a second sintering reaction, the kiln temperature is raised to 780°C, and the sintering is performed for 10 hours. The kiln is an atmosphere furnace with an oxygen concentration of ≥99.0%. The sintered material is then crushed and sieved to remove iron to obtain a secondary lithium low residual alkali positive electrode material of a certain particle size; recorded as SC12-NCM.

[0108] Comparative Example 2 This comparative example provides a ternary positive electrode material, the chemical formula of which is: LiNi 0.83 Co 0.12 Mn 0.05 Zr 0.0016 Al 0.005 8W 0.0016 O2. The difference from Example 1 is that the cobalt source in this comparative example has been added according to the set molar ratio before the first lithiation: Co: (Ni + Co + Mn) = 0.12:1.

[0109] The preparation method of the ternary positive electrode material comprises the following steps: 1) Ni precursor 0.83 Co 0.12 Mn 0.05 (OH)2 and LiOH were mixed in a molar ratio of Li: (Ni + Co + Mn) = 0.9:1; ZrO 2, In terms of molar ratio, the amount of ZrO2 satisfies Zr: (Ni + Co + Mn) = 0.12:100, and the amount of Al2O3 satisfies Al: (Ni + Co + Mn) = 0.58:100.

[0110] 2) The mixed materials are placed in a sagger of 330*330*120mm and sintered in an oxygen atmosphere furnace. The sintering conditions are: the kiln is first heated to 550℃ and kept warm for 5h, then heated to 720℃ and kept warm for 10h. The kiln is an atmosphere furnace with an oxygen concentration of ≥99.0%.

[0111] 3) The obtained sintered material is crushed to a certain particle size, and the remaining lithium source is added, and the molar ratio of Li: (Ni + Co + Mn) = 1.03:1 is adjusted, and high-speed dispersion is performed for 30 minutes. Then WO3 is added, wherein the amount of WO3 in terms of molar ratio satisfies W: (Ni + Co + Mn) = 0.16:100, and the mixture is evenly mixed and dispersed.

[0112] 4) The obtained coated material is subjected to a second lithium sintering reaction, the kiln temperature is raised to 780°C, and the sintering is performed for 10 hours. The kiln is an atmosphere furnace with an oxygen concentration of ≥99.0%. The sintered material is then crushed and sieved to remove iron to obtain a secondary lithium low residual alkali positive electrode material of a certain particle size; recorded as SC13-NCM.

[0113] The particle size distribution of the ternary positive electrode materials of Examples 1 to 11 and Comparative Examples 1 to 2 was tested respectively, and the results are shown in Tables 1 and Figure 2 The pH and residual alkali of the ternary positive electrode materials of Examples 1 to 11 and Comparative Examples 1 to 2 were tested respectively, and the results are shown in Table 1.

[0114] Table 1

[0115] From Table 1 and Figure 2 It can be seen that the particle size volume and number distribution of Examples 1 to 11 and Comparative Examples 1 to 2 are basically the same.

[0116] It can also be seen from Table 1 that, compared with Comparative Examples 1-2, the residual alkali contents Li2CO3 and LiOH of Examples 1-11 are significantly reduced, and the pH of Examples 1-11 is also significantly reduced. It can be seen that, since cobalt hydroxide is reacted twice into the system, the residual alkali on the surface of the particles can be further converted into nickel-cobalt-manganese-lithium oxide ternary materials during the sintering process, thereby achieving the purpose of reducing the residual alkali on the surface of the particles. In summary, the secondary lithiation of Examples 1-11 and the secondary addition of the cobalt source to the reaction system can better reduce the residual alkali on the surface of the material, thereby achieving the purpose of eliminating the traditional water washing process to reduce the residual alkali.

[0117] The ternary positive electrode materials of Example 1 and Comparative Examples 1-2 were observed by SEM, and the results were as follows: Figure 3 As shown. Figure 3 It can be seen that the preparation process of Example 1 can generate single crystal SC1-NCM with full particles; and the secondary lithiation sintering process of Example 1 has a low degree of cation mixing, good consistency of particle size, and is tightly combined to form uniform secondary particles with smooth surface. In Comparative Example 1, a single lithiation without water washing was performed to generate a ternary agglomerate SC12-NCM. It can be seen that single crystals were not completely generated in SC13-NCM of Comparative Example 2. This shows that in the secondary lithiation process, if only lithium salt is added during the second sintering process without adding a cobalt source, the surface lithium will be over-enriched, and agglomerates will be easily generated in local areas.

[0118] The XRD spectrum analysis was performed on the ternary positive electrode materials of Examples 1 to 11 and Comparative Examples 1-2 respectively. The crystal structures of the ternary positive electrode materials prepared in Examples 1 to 11 and Comparative Examples 1-2 were analyzed by XRD detection. The results are as follows: Figure 4 And as shown in Table 2.

[0119] Figure 4 The XRD spectrum analysis of Example 1 and Comparative Examples 1-2 shows that Figure 4 It can be seen that the diffraction peaks of the three materials are consistent with the layered structure of α-NaFeO2 (R3-m space group). In addition, the (006) / (012) and (018) / (110) double peaks corresponding to the 38° and 65° positions are obviously split, indicating that the materials have a good layered structure and exhibit good crystallinity. Further qualitative analysis of the Li5AlO4 impurity phase in the material was carried out. Specifically, Figure 4 In the XRD characterization analysis (b), in the diffraction patterns of SC12-NCM (Comparative Example 1 material) and SC13-NCM (Comparative Example 2 material), diffraction peaks characteristic of Li5AlO4 appeared at 2θ of 23.8°, 33.6°, and 33.8°. I (a) / I By comparing the intensity of the (003) characteristic peak, it was found that the proportion of SC1-NCM (material of Example 1) was 0.01%, while the intensity ratios of SC12-NCM and SC13-NCM were 2.39% and 0.78%, respectively. The diffraction peak intensity of the impurity phase in the SC1-NCM material (material of Example 1) was basically absent compared with that in Comparative Examples 1-2, indicating that the use of a secondary lithiation reaction and the addition of Al element during a high-temperature sintering can effectively inhibit the formation of the impurity phase Li5AlO4.

[0120] In the present invention, the lithium-ion battery is a CR2025 battery. The present invention preferably mixes the positive electrode material described in the above technical solution with a conductive agent (supper-P) and an adhesive (6% PVDF solution, the solvent is N-methyl-2-pyrrolidone) in a mass ratio of 80:10:10, and then supplements a small amount of N-methyl-2-pyrrolidone according to the viscosity of the slurry. The obtained electrode slurry is coated, dried, rolled and punched; the negative electrode is a lithium sheet; the 1mol / L LiPF6 is used as an electrolyte, and a polyolefin diaphragm is selected as the diaphragm. The positive electrode, diaphragm and negative electrode are assembled using a stacking process. After the button battery is assembled, it is placed in a constant temperature box at (25±2)℃ for 12 hours to test its electrical properties.

[0121] The lithium-ion button cells assembled from the above Examples 1-5 and Comparative Examples 1-2 were tested for discharge capacity at different charge and discharge rates of 0.1C / 0.1C, 0.2C / 0.2C, 0.33C / 0.33C, 0.5C / 0.5C, 1.0C / 1.0C, and 1.0C / 2.0C at 25°C and 3.0-4.3V; the capacity retention rate of the button cells was tested at 25°C, 3.0-4.3V, and 1.0C / 1.0C for 80 cycles.

[0122] Table 2

[0123] It should be noted that the units of a and c are both Å, and 1 Å=0.1 nm.

[0124] As can be seen from Table 2, the peak intensity ratios of I(003) / I(104) of SC1-NCM and SC13-NCM before half-battery cycling are 1.6009 and 1.4275, respectively, and I(003) / I(104)>1.2, indicating that the layered structure of the material is good and the lithium ion deintercalation process is not hindered, thereby improving the electrochemical performance of the battery. The peak intensity ratio of SC12-NCM is only 1.0733, which is less than 1.2, indicating that the degree of cation mixing in the layered positive electrode material is high, and the lithium ion deintercalation of the material is hindered, affecting the performance of the battery.

[0125] In addition, it can be seen from Table 2 that after SC1-NCM was cycled 80 times at 25°C, after parameter calculation, the peak intensity ratio of I(003) / I(104) of the material only dropped from 1.6009 to 1.5864, and the c / a values ​​before and after the cycle were 4.9560 and 4.9559, respectively, which were basically unchanged; while the I(003) / I(104) peak intensity ratios of SC12-NCM and SC13-NCM dropped from 1.0733 to 0.7996 and 1.4275 to 1.2274, respectively, with a significant decrease, and the c / a value also decreased to varying degrees, indicating that the Li / Ni ion mixing degree of the material increased after the cycle, resulting in changes in the wafer layer of the layered structure. SC1-NCM is the material prepared in Example 1, SC12-NCM is the material prepared in Comparative Example 1, SC13-NCM is the material prepared in Comparative Example 2, and the rules of Examples 2 to 11 are basically the same as those of Example 1, which will not be repeated here one by one.

[0126] Figure 5 This is a comparative analysis of the XRD spectrum of the positive electrode materials before and after cycling of Example 1 and Comparative Examples 1-2 of the present application. Figure 5 As shown in (ac) in the figure, the (006) / (102) and (108) / (110) peaks of SC1-NCM can be clearly separated in the XRD, while SC12-NCM and SC13-NCM are close to each other to varying degrees after cycling, indicating that during the cycling process, the integrity of the material layered structure is significantly weakened, the crystal structure is damaged, and the migration of lithium ions is hindered, resulting in cycling failure. The comprehensive XRD analysis before and after the cycle shows that the positive electrode material SC1-NCM obtained by the secondary lithiation multi-metal doping co-modification of the present application can not only reduce the content of Li5AlO4 during the sintering process, but also reduce the lithium-nickel mixing phenomenon during the material cycling process to a certain extent due to the stability of the crystal structure.

[0127] In this application, the ternary positive electrode materials of Examples 1 to 11 and Comparative Examples 1-2 are mixed with a conductive agent (supper-P) and an adhesive (6% PVDF solution, the solvent is N-methyl-2-pyrrolidone) in a mass ratio of 80:10:10, and then a small amount of N-methyl-2-pyrrolidone is added according to the viscosity of the slurry. The obtained electrode slurry is coated, dried, rolled and punched to obtain a positive electrode sheet. A lithium sheet is used as the negative electrode sheet. 1 mol / L LiPF6 is used as the electrolyte, and a polyolefin diaphragm is used as the diaphragm. The positive electrode sheet, diaphragm, and negative electrode sheet are assembled using a stacking process. After the button battery is assembled, it is placed in a constant temperature box at (25±2) ℃ for 12 hours to test its electrical properties.

[0128] The lithium ion button cells assembled in Examples 1 to 11 and Comparative Examples 1-2 were respectively tested for discharge capacity at different charge and discharge rates of 0.1C / 0.1C, 0.2C / 0.2C, 0.33C / 0.33C, 0.5C / 0.5C, 1.0C / 1.0C, and 1.0C / 2.0C at 25°C and 3.0-4.3V; the capacity retention rate of the button cells was tested at 25°C, 3.0-4.3V, 1.0C / 1.0C for 80 cycles, and the results are shown in Table 3.

[0129] Table 3

[0130] As can be seen from Table 3, compared with Comparative Examples 1 to 2, the capacity performance and rate performance of Examples 1 to 11 are significantly improved. In particular, the 0.1C / 0.1C rate charge and discharge of lithium ions assembled with the ternary positive electrode material of Example 1, the first discharge of SC1-NCM can reach 213.0mAh / g, and the first discharge efficiency can reach 92.7%, while SC12-NCM and SC13-NCM are only 195.7 and 201.4mAh / g, respectively. Similarly, the charge and discharge comparison at other rates shows that Example 1 is significantly higher than Comparative Examples 1-2.

[0131] Figure 6 1 is a trend diagram of the discharge capacity of the lithium ion batteries of Example 1 and Comparative Examples 1-2 at different rates. Figure 6 It can be seen that compared with Comparative Examples 1-2, the rate performance of Example 1 is more excellent. At the same time, it is found that the rate performance of Comparative Example 2 is also slightly better than that of Comparative Example 1. This shows that the battery of the single crystal positive electrode prepared by the secondary lithiation lithium supplementation and cobalt supplementation process exhibits a higher reversible capacity. In Comparative Example 2, since the cobalt source is added all at once during the first sintering, and is not added in stages, only the lithium source is added during the secondary sintering, resulting in a low degree of single crystalization and blurred single crystal interface. Therefore, the rate performance of Comparative Example 2 is lower than that of Example 1.

[0132] Figure 7 It is the retention rate of the button cells of Example 1 and Comparative Examples 1-2 after 80 cycles at 25°C, 3.0-4.3V, 1.0C / 1.0C. It can be seen from the figure that the cycle performance of the button cell of Example 1 is significantly better than that of Comparative Examples 1-2. After 80 cycles, the capacity retention rates of Example 1, Comparative Example 1 and Comparative Example 2 are 100.03%, 96.29% and 98.28%, respectively. Comparing Example 1 with Comparative Example 1, since the surface residual alkali of Comparative Example 1 is relatively high, during multiple charge and discharge cycles, the lithium ions in the agglomerated particles are repeatedly precipitated and re-embedded, and microcracks occur in the particles, resulting in rapid capacity decay. Comparing Example 1 with Comparative Example 2, since the particles of Comparative Example 2 are between single crystal and agglomerate, and the residual alkali content is also higher than that of Example 1, its capacity also has obvious capacity decay after 65 cycles.

[0133] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0134] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.

Claims

1. A positive electrode material, characterized in that: The chemical formula of the positive electrode material is Li 1~1.2 Ni x Co y Mn z M a Al b Q c O2, wherein M is selected from one of Zr, Mg, Y and Ti, Q is selected from one of W, V and B, 0.6≤x<1.0, 0<y≤0.2, 0<z≤0.2, 0.001≤a<0.004, 0.004≤b<0.008, 0.001≤c<0.03; The positive electrode material is a layered structure of single crystal α-NaFeO2. In the XRD spectrum of the positive electrode material, there are characteristic peaks (006) and (102) with a bimodal distribution at 2θ of 37° to 39°, and there are characteristic peaks (018) and (110) with a bimodal distribution at 2θ of 64° to 66°. After the positive electrode material is cycled 80 times under the conditions of 25°C, 3.0V~4.3V, 1.0C / 1.0C, the change value of the unit cell parameter c / a satisfies , wherein a represents the length of the positive electrode material along the crystal a-axis before the cycle, c represents the length of the positive electrode material along the crystal c-axis before the cycle, a' represents the length of the positive electrode material along the crystal a-axis after 80 cycles, and c' represents the length of the positive electrode material along the crystal c-axis after 80 cycles.

2. The positive electrode material according to claim 1, characterized in that In the XRD spectrum of the positive electrode material, the ratio of the peak intensity I(003) on the (003) crystal plane to the peak intensity I(104) on the (104) crystal plane satisfies: 1.2 <I(003) / I(104)<1.7; And / or, after the positive electrode material is cycled 80 times under the conditions of 25°C, 3.0V~4.3V, 1.0C / 1.0C, the change value of the I(003) / I(104) peak intensity ratio satisfies ; Wherein I'(003) is the peak intensity of the characteristic peak corresponding to the (003) crystal plane of the positive electrode material after 80 cycles, and I'(104) is the peak intensity of the characteristic peak corresponding to the (104) crystal plane of the positive electrode material after 80 cycles.

3. The positive electrode material according to claim 1, characterized in that In the XRD spectrum of the positive electrode material, the peak intensity I of the characteristic peak at 2θ=33.7°-34.0° is a The ratio of the peak intensity I(003) on the (003) crystal plane satisfies: 0.001≤I a / I(003)≤0.

1.

4. The positive electrode material according to any one of claims 1 to 3, characterized in that The pH value of the positive electrode material is less than 11.7, the residual alkali content in the positive electrode material is less than 3500 ppm, the residual alkali in the positive electrode material includes LiOH and Li2CO3, and the ratio of the content of LiOH in the residual alkali to the content of Li2CO3 in the residual alkali is 0.1~0.

8.

5. The positive electrode material according to claim 4, characterized in that The content of LiOH in the positive electrode material is less than 1100 ppm, and the content of Li2CO3 in the positive electrode material is less than 3000 ppm.

6. A method for preparing the positive electrode material according to any one of claims 1 to 5, characterized in that: include: (1) mixing a nickel-cobalt-manganese precursor, a portion of a lithium source, a metal doping element M source, and an Al source according to a stoichiometric ratio, and performing a first sintering to obtain a first sintered product; (2) The first sintered product, the remaining lithium source, the cobalt source and the metal coating element Q source are mixed according to a stoichiometric ratio to form a mixed material, and a second sintering is performed to obtain a single crystal positive electrode material.

7. The method according to claim 6, characterized in that In step (1), the amount of the partial lithium source added satisfies the molar ratio of Li element to the sum of transition metal elements in the nickel-cobalt-manganese precursor of Li:(Ni+Co+Mn)=(0.85-0.95):1; And / or, in step (1), the molar ratio of the Co element in the nickel-cobalt-manganese precursor to the sum of the transition metal elements in the nickel-cobalt-manganese precursor is Co:(Ni+Co+Mn)=(0.07-0.11):1; And / or, in step (1), the amount of the Al source added satisfies the molar ratio of Al element to the sum of transition metal elements in the nickel-cobalt-manganese precursor of Al:(Ni+Co+Mn)=(0.004-0.008):1; And / or, in step (1), the amount of the M source added satisfies the molar ratio of the M element to the sum of the transition metal elements in the nickel-cobalt-manganese precursor being M:(Ni+Co+Mn)=(0.001-0.004):

1.

8. The method according to claim 6, characterized in that In step (2), the amount of the Co source added satisfies the following molar ratio in the mixed material: Co:(Ni+Co+Mn)=(0.10-0.14):1; And / or, in step (2), the amount of the remaining lithium source added satisfies the following molar ratio in the mixed material: Li:(Ni+Co+Mn)=(1.01-1.2):1; And / or, in step (2), the amount of the Q source added satisfies the following molar ratio in the mixed material: Q:(Ni+Co+Mn)=(0.001-0.03):

1.

9. The method according to claim 6, characterized in that The chemical formula of the nickel-cobalt-manganese precursor is Ni x Co y Mn z (OH)2, where 0.6≤x<1.0, 0<y≤0.2, 0<z≤0.2; And / or, the lithium source comprises LiOH·H2O, and the particle size D50 of the lithium source satisfies 12.0 μm≤D50≤18.0 μm; And / or, the metal doping element M source is an oxide, hydroxide, oxalate, organic alcohol salt or carbonate containing the element M, and the particle size D50 of the M source satisfies 0.5 μm≤D50≤0.6 μm; And / or, the Al source is selected from Al2O3, and the particle size D50 of Al2O3 satisfies 15nm≤D50≤25nm; And / or, the metal coating element Q source includes WO3, and the particle size D50 of WO3 satisfies 30nm≤D50≤300nm; And / or, the cobalt source comprises cobalt hydroxide.

10. The method according to claim 6, characterized in that In step (1), the first sintering is to first heat the temperature to 450°C-550°C in an oxygen atmosphere, keep the temperature for 4h-5h, then heat the temperature to 700°C-750°C, and keep the temperature for 10h-15h; And / or, the first sintered product is crushed, screened and iron-removed, and the particle size distribution of the first sintered product after crushing, screening and iron-removal satisfies: D1≥1.0μm, 3.0μm≤D50≤5.0μm, D100≤15.0μm, and the total content of magnetic foreign matter is ≤60ppm.

11. The method according to claim 6, characterized in that In step (2), the second sintering is performed by heating the mixture to 730°C to 800°C in an oxygen atmosphere and sintering for 10h to 15h; And / or, the second sintered product is crushed, screened and iron-removed to obtain the positive electrode material, wherein the particle size distribution of the positive electrode material satisfies: D1≥1.0μm, 3.0μm≤D50≤5.0μm, D100≤15.0μm, and the total content of magnetic foreign matter is ≤60ppm.

12. A positive electrode sheet, characterized in that: The invention comprises the positive electrode material according to any one of claims 1 to 5 or the positive electrode material prepared by the method according to any one of claims 6 to 11.

13. A battery, characterized in that: Including the positive electrode sheet as described in claim 12.

14. An electrical device, characterized in that: Comprising the battery of claim 13.

Citation Information

Patent Citations

  • Lithium ion battery cathode material and preparation method thereof, cathode and lithium ion battery

    CN109461926A

  • Positive electrode material, preparation method thereof and lithium ion battery

    CN115472838A

  • Method for reducing residual alkali of single-crystal positive electrode material, single-crystal positive electrode material and lithium ion battery

    CN116835672A

  • Positive electrode active material and preparation method thereof, positive electrode plate, battery and electric equipment

    CN118919699A

Cited By

  • Battery cycle performance evaluation method and system, electronic equipment and storage medium

    CN120870898A

  • A battery cycle performance evaluation method and system, electronic device, and storage medium

    CN120870898B

  • Ternary positive electrode material with coating layer, preparation method of ternary positive electrode material, positive electrode and battery

    CN121149213A

  • Positive electrode material and preparation method thereof, positive plate and lithium ion battery

    CN121726402A

  • Positive electrode material, surface-reconstructed material and lithium-ion battery

    WO2026153429A1